Retorika Kalam Insyā' Ṭalabī dalam Kitab Riyāḍ al-Ṣāliḥīn: Studi Balaghah pada Bab Adab 84–99 - Abdul Aziz; Rohanda Rohanda; Yayan Rakhtikawati (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2026)
Kalam insyā’ ṭalabī is one of the important topics in balāghah studies because it functions to reveal the speaker's communicative intentions through forms of expression such as commands, prohibitions, questions, wishes, and vocatives. Although Riyadhus Shalihin has been widely studied from the perspectives of hadith and ethics, research that specifically analyzes kalam insyā’ ṭalabī from the perspective of ‘ilm al-ma‘ānī in the Adab chapters 84–99 remains relatively limited. This study aims to examine the forms and meanings of kalam insyā’ ṭalabī found in the book Riyāḍhuṣ Ṣāliḥīn by Imam an-Nawawī, particularly in the Adab chapters 84–99. The focus of this study is to identify the types of kalam insyā’ ṭalabī, such as amr, nahy, istifhām, tamannī, and nidā’, as well as to analyze the rhetorical meanings contained within them. This research employs a qualitative approach using a descriptive-analytical method and a linguistic-rhetorical analytical framework. The primary data sources are the hadiths in Riyadhus Shalihin Adab chapters 84–99 that contain elements of kalam insyā’ ṭalabī. Data collection techniques were carried out through library research and textual analysis of the hadiths that became the object of the study. The data were analyzed using the distributional method with deletion techniques to determine the forms of utterances, followed by contextual and rhetorical approaches based on the perspective of ‘ilm al-ma‘ānī to reveal the functions and meanings contained in each form of kalam insyā’ ṭalabī. The results of the study indicate that kalam insyā’ ṭalabī in these hadiths functions not only as literal commands or prohibitions, but also conveys meanings of advice, guidance, warning, and moral education delivered in a communicative and persuasive manner